Automatic fuzzy-neural based segmentation of microscopic cell images. (15th April 2008) - Colantonio, Sara; Gurevich, Igor B.; Salvetti, Ovidio
In this paper, we propose a novel, completely automated method for the segmentation of lymphatic cell nuclei represented in microscopic specimen images. Actually, segmenting cell nuclei is the first, necessary step for developing an automated application for the early diagnostics of lymphatic system tumours. The proposed method follows a two-step approach to, firstly, find the nuclei and then, to refine the segmentation by means of a neural model, capable of localising the borders of each nucleus. Experimental results have shown the feasibility of the method.